Fresh Enterprise Catfish Farming / Mawardi Abd Gani ... [et al.] - Abd Gani, Mawardi; Samsul, Kartini; Hamka Dol, Syahiratun Nadia; John Frankie, Diaswilson; Latuwoh, Noor Hazmiza (2009)
After decision making with all member of group, we choose the catfish with omega 3 farming. We will produce and supplying according to the market demand nowadays. Our activities begin from until marketed to the customer. Type of business that we choose is partnership. Each member or partner of business will be contributing our capital for start our business. We choose the catfish with omega 3 farming because omega3 only can get in before starting this business, all of us go to the Sabah Agricultural Department to get information about how to farm the catfish with omega3 and others information.